B-CLL with negative 18F-FDG PET/CT and intensive solitary lesion on PSMA PET/CT mimicking prostate cancer bone metastases - Theresa Jung; Daniel Neureiter; Gregor Schweighofer-Zwink; Gundula Rendl; Christian Pirich; Mohsen Beheshti (EJNMMI Reports)
Abstract Positron emission tomography/computed tomography (PET/CT) using prostate-specific membrane antigen (PSMA)-radioligands is currently suggested by several clinical guidelines for the assessment of prostate cancer (PCa) in various clinical settings. However, PSMA will also be overexpressed in different cancers, which should be considered on the PSMA PET/CT reading in patients with concomitant neoplastic diseases. We report a case of 82-year-old male presented with prostate and history of oesophageal cancer and B-cell chronic lymphocytic leukemia (B-CLL). Both 68Ga-PSMA-11 and 2-(3-(1-carboxy-5-((6-(18f)fluoro-pyridine-3-carbonyl)-amino)-pentyl)-ureido)-pentanedioic acid (18F-DCFPyL) PET/CT, which were performed for prostate cancer staging and re-staging in about 1 year interval, showed focal uptake in the primary prostate tumor as well as an intense focal lesion in L2, suggestive of bone metastasis. 18F-FDG PET/CT scans performed before and after PSMA PET/CT examinations showed no abnormal uptake related to oesophageal and/or B-CLL. This pattern could present an oligometastatic PCa disease, which might change the treatment plan of the patient to radiation of the bone metastasis. However, bone biopsy of the detected lesion on L2 revealed infiltrates of B-CLL. The role of 68Ga- and 18F-labeled PSMA PET/CT in prostate cancer is evolving and has been demonstrated to have high sensitivity, but may present limited specificity in patients with coexisting cancer(s), which should be considered in PSMA PET/CT reading.